2008
DOI: 10.1111/j.1440-172x.2008.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' work environment and nursing outcomes: A survey study among Finnish university hospital registered nurses

Abstract: The aim was to assess the interrelationships between nurses' work environment and nursing outcomes. A cross-sectional survey of 664 registered nurses (RN) on 34 acute care inpatient hospital wards was used to measure nurses' perceptions. Patient data (n = 4045) consisting of a total patient satisfaction indicator were collected simultaneously with the nurse data during year 2005. RN's assessments of staffing adequacy, respect and relationships were the most important factors of work environment having an influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 24 publications
3
44
0
1
Order By: Relevance
“…These results imply that proper strategies could increase nurse retention rate in healthcare organizations. This outcome was similar to that of previous studies, indicating that nurses in poor practice environments showed a higher rate of turnover intent than those in better practice environments [7,26,27] . Also, Patrician et al [20] reported that nurses working in unfavorable working environments were three times more likely to leave their job.…”
Section: Discussionsupporting
confidence: 81%
“…These results imply that proper strategies could increase nurse retention rate in healthcare organizations. This outcome was similar to that of previous studies, indicating that nurses in poor practice environments showed a higher rate of turnover intent than those in better practice environments [7,26,27] . Also, Patrician et al [20] reported that nurses working in unfavorable working environments were three times more likely to leave their job.…”
Section: Discussionsupporting
confidence: 81%
“…For example, Applebaum and colleagues (Applebaum, Fowler, Fiedler, Osinubi, & Robson, 2010) found a significant relationship between noise and nurses' perceived stress. Finally, it is also plausible that the effect of the physical environment on staff stress is masked and mediated by other more relevant or proximal factors such as shift work, workload, support, or other factors of the organizational and social environment (Chan & Huak, 2004;Cooper, Rout, & Faragher, 1989;Gray-Toft & Anderson, 1981;Sutherland & Cooper, 1993;Tervo-Heikkinen, Partanen, Aalto & Vehvilainen-Julkunen, 2008). For all these reasons, the relationship between the physical conditions of the workplace and the stress of healthcare professionals needs verification in further research.…”
Section: Discussionmentioning
confidence: 99%
“…Hataların oluşumunu ya da tekrarını önlemek için, düzenli olarak eğitimler verilmesi, bildiriminin yapılması, düzeltici çalışmaların planlanması ve izlenebilirliğin sağlanması gerekmektedir 33,34 . Çalışma ortamındaki stres ve uygunsuz çevresel faktörler de hatalara neden olabileceğinden, ortam şartları sağlıklı uygulama için uygun hale getirilmelidir 35,36 . V4'te uygulama ve izleme süreci ile ilgili 26 kriter bulunmaktayken; V5'te 10 kriter bulunmaktadır.…”
Section: Gereç Ve Yöntemunclassified